Being Indonesian, being Chinese: searching for a third space between ethnicity and nationality among Chinese Indonesian Buddhists - Khu, Stanley (Religion, 2026)
This paper discusses the religious practices and beliefs of Chinese Indonesians who adhere to the Vajrayana tradition of Tibetan Buddhism to explore the emergence of Homi Bhabha’s ‘third space’ that may reconcile the tense relationship between ethnicity and nationality among Chinese Indonesians. Through ethnographic study in Kadam Choeling Indonesia (KCI), a community of Chinese Indonesian Vajrayana adherents, I discuss how KCI Buddhists utilize their religious identity to navigate and negotiate their national and ethnic identities. My findings demonstrate that their religious identity as Vajrayana adherents facilitates the emergence of a third space that accommodates the simultaneous existence of ethnic and national identities. This concurs with similar studies conducted among Chinese Indonesians who profess other religious traditions like Christianity or Islam. By providing a comparative note, I point out some similarities and differences in how the third space emerges in respective religious settings.